Barriers to ICTs Adoption in SMEs: Evidence From a Developing Country Perspective - Ongori, Henry (Prabandhan: Indian Journal of Management, 2008)
Small and Medium Enterprises (SMEs) contribute a lot to the economy of both developing and developed countries in terms of diversification of the economic activities and in job creation. However, SMEs are not strategically positioned to compete with large enterprises due to lack of ICTs adoption. The purpose of this study was to find out the major constraints to ICTs adoption in SMEs. The methodology adopted in this study was a convenience random sampling of 250 managers/owners of SMEs in Gaborone capital city and its surroundings, in Botswana. The findings of the study indicated that the major barriers to ICTs adoption in SMEs are lack of infrastructure, managers are not aware of ICTs benefits, and lack of security in ICTs tools usage. The study will make a relevant contribution to body of knowledge and provoke debate amongst managers of SMEs to come up with the best strategies to resolve these barriers. The limitation of the study is that the sample size of SMEs selected was small to generalize the results.